Role of Bile Acid Pathway Intermediates in Pathology of CTX - William Griffiths (2023)
A deficiency in the enzyme sterol 27-hydroxylase (CYP27A1) leads to the autosomal recessive disorder cerebrotendinous xanthomatosis (CTX). CYP27A1 catalyses the first steps of the acidic pathway of bile acid biosynthesis. Most cells express CYP27A1, and a deficiency in this enzyme results in the activation of shunt pathways to help remove excess cholesterol. CYP27A1 also appears in the middle of the neutral pathway of bile acid biosynthesis and its deficiency results in accumulation of up-stream pathway intermediates. Here we describe methods for the simultaneous analysis of almost all metabolites from cholesterol to bile acids in a single assay and discuss the relative importance of accumulation of pathway intermediates and missing metabolites to the pathology of CTX.